Smart Waste Collector Boat for Lake - Awang, Mohd Azizul; Ahmad, Nabihah (Evolution in Electrical and Electronic Engineering, 2021)
This paper discusses the ’Smart Waste Collector Boat,’ which collects waste from the lake’s surface. The project was designed using Solidworks software and sketched in Fritzing software. The boat was constructed using recycled materials. Because it is lightweight and waterproof, this boat may float on the water’s surface. The latest electronic component such as Arduino Uno, battery 12 V, PIR Sensor, motor module (L298N) and Bluetooth module (HC-05) have been installed at the circuit. The boat is controlled with an Arduino Bluetooth controller apps by using a smartphone. The boats can move and collect garbage from the surface of the lake. This initiative has the potential to solve the issue of water, air, and smell pollution.